Investigation of Plasma Filter Influence on Ions Charge State of DC Vacuum Arc Plasma; 7 International conference on modification of materials with particle beams and plasma flows - Sinebryukhov A. A.; Dektyarev S. V. Sergey Valentinovich; Ryabchikov A. I. Aleksandr Ilyich; Stepanov I. B. Igor Borisovich (Beam and plasma sources, 2004)
Title from the title-page.